Radiation moms’ organizational survival for a decade: A shift from advocacy to non-advocacy activities - Löschke, Ayaka (Contemporary Japan, 2022)
This article examines changes in Japan’s social movement organizations (SMOs) after the Fukushima Daiichi nuclear disaster, focusing on mothers against radiation as key actors. After the Fukushima disaster, Japan’s SMOs enjoyed not only a resurgence of mass protests, but also an increase in advocacy activities and mothers’ participation in relation to radiation protection. Furthermore, some mothers’ SMOs against radiation survived for a decade. Such longevity is internationally unusual for an SMO. However, these SMOs have been virtually unstudied with regards to this longevity. How did mothers’ SMOs against radiation fight for survival for more than a decade? To answer this question, this project conducted long-term ethnographic research on a mothers’ SMO, the Kodomo-tachi o Hōshanō kara Mamoru Zenkoku Nettowāku (the National Network of Parents to Protect Children from Radiation; the “Kodomozenkoku”). Founded in 2011, Kodomozenkoku has been active for more than a decade. It recruited over 350 local SMOs as rank-and-file and shifted its focus from national advocacy activities to local non-advocacy activities. Based on this case study of Kodomozenkoku, this research argues that Kodomozenkoku’s flexibility in its transformation concerning goals, internal structure and interorganizational relations enabled this newcomer SMO to survive for over a decade.<br
Keywords: Fukushima; social movement; civil society; mothers; advocacy; organizational transformation